An innovative solar energy-powered floating media bed reactor for nutrient removal (II): material characterization. (1st October 2016) - Lin, Kuen-Song; Chang, Ni-Bin; Hartshorn, Nickolas; Wanielista, Martin P.; Chiang, Chao-Lung
Abstract: To enhance the removal efficiencies of total phosphorus (TP) and total nitrogen (TN), a Floating Media Bed Reactor (FMBR) was developed as a supplementary treatment unit for stormwater wet detention ponds. The FMBR was filled with an engineered mixture of media for the removal of target nutrient species. These materials aid in the physiochemical sorption and precipitation of orthophosphates as well as in the biological transformation of ammonia, nitrates and nitrites. The microstructure and morphology of the green media has not been well studied in recent years, however, because this is a new topic of interest. Therefore, the main objective of this study was to characterize the fine structures and morphology of the green media utilized in the FMBR. Experimentally, field-emission scanning electron microscopy (FE-SEM) micrographs reveal biofilms on the surface of porous media that likely enhanced the removal efficiency of TN and TP during field operation. From the X-ray powder diffraction (XRD) patterns, hexagonal-typed SiO2 and monoclinic-typed Al2 O3 are characteristics of average crystallite sizes of 200–250 nm for fresh and used media samples. The media possess numerous pores or cavities where nutrients can easily be adsorbed. Moreover, the Brunauer–Emmett–Teller (BET) specific surface area (pore volume) decreased from 33 to 25 m 2  g −1 (0.16–0.10 cm 3  g −1 ) after field testing the FMBR. These results suggest that voids in post-treatment media samples were filled or occupied with nutrients and particulates adsorbed onto the media surface or biofilms, thus leading to the reduction of BET specific surface area and pore volume. The post-treatment adsorbent media had a slightly stronger stretching vibration of POC and POP species around 600 and 800 cm −1 respectively, found in the Fourier transform infrared (FTIR) spectra, which may be explained by more nutrients having been adsorbed on the surface or biofilms of the porous structures. Highlights: Floating media bed reactor can remove nutrients in stormwater wet ponds efficiently. Solar power can sustain all operational need in the ponds. Green sorption media contribute to the overall performance of nutrient control.